The Tyrosine Kinase Inhibitor Nilotinib Selectively Inhibits CYP2C8 Activities in Human Liver Microsomes - Kim, Min-Jung; Lee, Jae-Won; Oh, Kyung-Suk; Choi, Chang-Soo; Kim, Kwang Hee; Han, Won Seok; Yoon, Chang-No; Chung, Eun Sook; Kim, Dong-Hyun; Shin, Jae-Gook (JAPANESE SOC STUDY XENOBIOTICS, 2013)
The tyrosine kinase inhibitor nilotinib was examined for its inhibition of cytochrome P450s (CYPs) in human liver microsomes and in human CYPs expressed in a baculovirus-insect cell system. Nilotinib demonstrated preferential inhibition of CYP2C8-mediated paclitaxel 6 alpha-hydroxylation, rosiglitazone hydroxylation and amodiaquine N-deethylation in human liver microsomes, with IC50 values of 0.4, 7.5 and 0.7 mu M, respectively. The IC50 value of nilotinib for paclitaxel 6 alpha-hydroxylation was 20-fold lower than that of the other five tyrosine-kinase inhibitors tested. Nilotinib appears to display competitive inhibition against paclitaxel 6 alpha-hydroxylation and amodiaquine N-deethylation, with estimated mean K-i values of 0.90 and 0.15 mu M in human liver microsomes and 0.10 and 0.61 mu M in recombinant human CYP2C8, respectively. These results are consistent with those of molecular docking simulations, where paclitaxel could not access the CYP2C8 catalytic site in the presence of nilotinib, but the binding of midazolam, a substrate of CYP3A4, to the catalytic site of CYP3A4 was not affected by nilotinib. The demonstrated inhibitory activity of nilotinib against CYP2C8 at concentrations less than those observed in patients who received nilotinib therapy is of potential clinical relevance and further in vivo exploration is warranted.
Keywords: IN-VITRO; BCR-ABL; AMINOPYRIMIDINE INHIBITOR; HEALTHY PARTICIPANTS; PHARMACOKINETICS; CYTOCHROME-P-450; OXIDATION; QUINIDINE; LEUKEMIA; AMN107